Dysregulation of the microbiota-gut-brain axis induced by chronic pancreatitis mediates anxiety- and depression-like behaviors in mice - Liu, Leheng; Zhang, Xi; Wang, Chuanyang; Zhou, Kena; Bao, Jingpiao; Cheng, Zhiyuan; Sun, Haoran; Zhu, Chengying; Yu, Ge; Xiao, Wenqin; Wan, Rong (Frontiers in Immunology, 2026)
BackgroundAnxiety and depression are common psychological complications in patients with chronic pancreatitis (CP). This study aims to investigate the dysregulation of microbiota-gut-brain axis induced by CP in driving anxiety- and depression-like behaviors in mice.MethodsC57BL/6J mice injected with caerulein (Cae) were used to establish an experimental CP model. Behavioral tests were performed to assess anxiety- and depression-like behaviors. The gut microbiota composition and serum metabolites were analyzed via 16S rRNA sequencing and liquid chromatography–mass spectrometry, respectively. Antibiotic cocktail (ABX) and fecal microbiota transplantation (FMT) models were employed to validate the direct role of the gut microbiota, while mixed probiotic gavage was used for intervention evaluation.ResultsCae-injected mice presented typical CP symptoms and significant anxiety- and depression-like behaviors. 16S rRNA sequencing revealed altered gut microbiota composition in CP mice, with a reduced abundance of Lactobacillus and enrichment of Helicobacter. ABX and FMT experiments confirmed that the CP-derived gut microbiota can independently induce anxiety/depression-like behaviors. In CP mice, Serum corticosterone and its metabolite levels were significantly increased in CP mice. CP-induced microbiota dysbiosis can induce the downregulation of intestinal barrier and blood–brain barrier functions, increase inflammatory levels, and extensively dysregulate neurotransmitter transmission in the brain. Treatment with mixed probiotics improved anxiety- and depression-like behaviors in CP mice.ConclusionsCP promotes anxiety- and depression-like behaviors in mice by inducing gut microbiota dysbiosis. This study provides experimental evidence for the use of microbiota-targeted interventions for treating the psychological complications of CP.